IMPLEMENTASI PERLINDUNGAN KONSUMEN DALAM JUAL BELI PRODUK MY FEET DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Afrida, Puspa; Dwi Nurahman; Kartika Sari (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
The purpose of this research is to determine the implementation of Act Number 8 of 1999 concerning Consumer Protection. This research includes a typology of empirical juridical research. The results of this study will show that the implementation of Consumer Protection as regulated in Act Number 8 of 1999 in dispute resolution mediation sessions held at BPSK is divided into 2 stages, namely; before the trial and during the trial process. The protection provided before the trial takes place, namely by providing services in receiving consumer reports and lawsuits, summoning business actors, selecting methods used in resolving disputes and appointing a dispute resolution trial panel, this is the implementation of the basic principles of consumer protection and the regulations of Act Number 8 of 1999 concerning Consumer Protection, which in its implementation is in accordance with Consumer Rights, Business Actors' Obligations and Business Actors' actions which are prohibited in sales and purchase agreements, with the presence of elements of defective will, lack of consumer awareness and weak law enforcement officials are indicators that consumer protection is not yet effective. Consumers have not fully exercised their rights as disadvantaged consumers Kata kunci : Perlindungan Konsumen, Jual Beli, Produk My Feet